Cross-Sectional Study of Leptospira spp. and Brucela abortus in Goat Herds from Paraná State, Brazil - Pasquali, Aline Kuhn Sbruzzi; Chideroli, Roberta Torres; Benitez, Aline do Nascimento; Caldart, Eloiza Teles; Evers, Fernanda; Fortes, Maira Salomão; Ferreira, Fernanda Pinto; Monteiro, Keila Clarine; Giordano, Lucienne Garcia Pretto; Freire, Roberta Lemos; et al. (Acta Scientiae Veterinariae, 2017)
Background: Leptospirosis and brucellosis are zoonosis worldwide distributed that have great economic importance, especially in goats. This study aimed to carry out a cross-sectional study to determine the prevalence of anti-Leptospira spp. and anti-Brucella abortus antibodies and to determine epidemiological variables associated to infection by these ethiological agents in goats. Materials, Methods & Results: Serum samples were collected from 1055 goats of 95 properties distributed in 18 regional centers of Paraná State from April to August of 2010. Collected samples were submitted to microscopic agglutination test (MAT) for the detection of anti-Leptospira spp. antibodies with 22 reference serovars: Australis, Bratislava, Autumnalis, Butembo, Castellonis, Bataviae, Canicola, Fortbragg, Whitcombi, Cynopteri, Grippotyphosa, Hebdomadis, Copenhageni, Icterohaemorrhagiae, Panama, Pomona, Pyrogenes, Hardjo, Wolffi, Shermani, Tarassovi and Londrina 1 (L1). The samples were also submitted to buffered acidified plate antigen test (BAPA) and 2-mercaptoethanol test (2-ME) to detect anti-Brucella abortus antibodies. The results obtained from epidemiological and serological study were analysed by Epi Info 3.5.3. We observed 9.9% (104/1055) of goats reagents in at least one serovar of Leptospira spp. and no reagent animal to Brucella abortus. The variables that were statistically significant with leptospirosis were: production type meat, sewer destination in dry sump, frequent abortion, shared use of pastures, slaughter of animals on the property, the presence of pigs and wild animals such as deer and capybaras on the property. Discussion: This was the first study about antibodies prevalence against Leptospira spp. and Brucella abortus in goat herds from Paraná State. The presence of both animal species were statiscally associated to risk of leptospirosis. It is necessary avoid the acess of these animals in herds, decreasing the dissemination of the agent. The production type meat is a form of creation in which the animals have no care of zookeepers and continuous veterinary care. The final destination of sewage was statistically associated to risk of leptospirosis in goats and this is a big problem in rural properties, requiring greater attention of authorities for proper disposal of this wastewater, reducing water and food contamination. Among the variables related to management, the herds that used rented pasture or shared pastures also were statistically associated to risk of leptospirosis in goats; with the sharing of pastures a greater flow of animals transiting in the pickets occurs, allowing not only flocks of goats, but other species also, to use the same pastures and become more exposed to certain diseases. The slaughter of pigs, sheep, cattle and goats on the property is a problem for animal and human health due to lack of sanitary inspection. Abortion is one of the main clinical signs of leptospirosis in farm animals, particularly goats. The knowledge of these results will be useful to develop control programs for the disease in Paraná State herds. The absence of circulating anti-Brucella abortus antibodies in goat herds has also been reported in other Brazilian States.